THE STRATEGY OF MANAGERS IN MOVING BUSINESS LEARNING GROUP PROGRAM IN PKBM SRIKANDI CIMAHI CITY - Dinno Mulyono (Kopertis Region IV Jabar and Banten, 2018)
This research is one way in describing the strategy of managers in moving the business group learning program for street children developed in PKBM Srikandi Kota Cimahi. Business group learning program is one of the containers in building independence for youth and street children who are expected to build entrepreneurial character. The purpose of this study is to describe the strategies undertaken by managers in moving the group learning business program. The theory underlying this research is the Concept of Management Unit Outside School Education, Concept Group Business Learning, Street Children Concept. The method of this research is qualitative descriptive with data collection technique using interview, observation and documentation study. The results obtained show that the group manager of PKBM Srikandi uses a persuasive approach in fostering self-confidence in the learning community, using motivation to encourage self-reliance in creative and solu- tive thinking, and using a test case approach to build resilience in developing a business. This research resulted in the conclusion that humanist, communicative and motivative management strategy able to build and develop self-reliance learners to develop their business independently.